Prevalence, pathophysiology and management of itch in epidermolysis bullosa. (29th November 2020) - Papanikolaou, M.; Onoufriadis, A.; Mellerio, J.E.; Nattkemper, L.A.; Yosipovitch, G.; Steinhoff, M.; McGrath, J.A.
Summary: Epidermolysis bullosa (EB) is a highly diverse group of inherited skin disorders, resulting from mutations in genes encoding proteins of the dermoepidermal junction. Itch (pruritus) is one of the most common symptoms across all EB subtypes. It occurs in blistered or wounded sites, or manifests as a generalized phenomenon, thereby affecting both intact skin and healing wounds. The mechanism of pruritus in EB is unclear. It is likely that skin inflammation secondary to barrier disruption, wound healing cascades and dysregulated activation of epidermal sensory nerve endings are all involved in its pathophysiology on the molecular and cellular level. Understanding these mechanisms in depth is crucial in developing optimized treatments for people with EB and improving quality of life. This review summarizes current evidence on the prevalence, mechanisms and management of itch in EB.